DEVELOPMENT OF PBL-BASED LKPD ON HUMAN DIGESTIVE SYSTEM MATERIAL FOR GRADE VIII JUNIOR HIGH SCHOOL - Andini, Risnada Adelia; Fardhani, Indra; Hamimi, Erti (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
This study aims to develop Problem-Based Learning (PBL) based learning media LKPD for the Digestive System material for Grade VIII Junior High School, and to test the validity and practicality of the product. The development of PBL-based LKPD is expected to assist educators in the learning process. This research is a development research (R&D) using the ADDIE model. The research instruments used are expert validation questionnaires for media experts and material experts, practitioner validation questionnaires given to junior high school science teachers (n = 4), and readability test questionnaires given to 4 classes of Grade VIII Junior High School students (n = 108). This study uses descriptive quantitative analysis for data analysis. Based on the data obtained, the media validation results are 95.24%, material validation results are 87.78%, practicality validation results are 90.16%, and an average score of 84.46% was obtained in the readability test. Thus, the PBL-based LKPD on the digestive system material falls into the category of being very valid and very practical for facilitating learning in education.